Prevalence of depression in mothers of intellectually disabled children: A cross-sectional study - Gourav Chandravanshi; Krishan Kumar Sharma; Charan Singh Jilowa; Parth Singh Meena; Mahendra Jain; Om Prakash (Medical Journal of Dr. D.Y. Patil University, 2017)
Background: Intellectual disability (ID) is a permanent and highly disabling condition. The birth of a disabled child induces complex feelings in mother and other family members. This study was planned to investigate phenomenology of ID and the prevalence of depression in their mothers. Objective: To find prevalence, influence of various sociodemographic variables, and its clinical correlation with depression in mothers of ID children. Study Design: A cross-sectional study. Materials and Methods: A total of 100 patients diagnosed as ID were included in the study. Objective data were collected in a special Pro forma, and mothers of these patients were evaluated with the Beck's Anxiety Inventory and Beck's Depression Inventory. Results: The mean age of patients with ID was 11.52 years, had received an average of 3.01 years of schooling, mean age at diagnosis was 6.01 years, mean intelligence quotient was 45.17, and 79% had significant comorbidities. The prevalence of depression in mothers was 79%; it was more in mothers of female ID child, ID child with significant comorbidities, severer forms of retardation, and with higher levels of anxiety in the mother. Conclusions: The prevalence of depression in mothers of ID children in the present study seems to be much greater than those reported from the previous studies. The determination of predictors of depression among mothers of ID children may help health professionals in identifying mothers at risk. Regular screening of mothers of ID children should be included in the protocol for management.